Pengaruh Kemampuan Pengelolaan Laboratorium Biologi UIN Sunan Gunung Djati Bandung - Raya Oktavia; Irawan Irawan; Tedi Priatna (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
The excellence of a biology education laboratory can be reflected in the quality and management profile it carries out. The purpose of this study was to determine the management system that is implemented in the Biology Education Integrated Laboratory at UIN Bandung. The research method uses a qualitative and descriptive method approach. The results showed that the implementation of laboratory management was classified as less than optimal and only part of it was running according to standard management rules. This is evidenced by the measurement results of planning indicators (planing) of 51.72% indicating positive or the